Additional new species of the genus Pterodichopetala (Phaneropteridae: Phaneropterinae) from Northeastern Mexico - Rocha-Sánchez, Aurora Yazmín; Barrientos-Lozano, Ludivina; Zaldívar-Riverón, Alejandro (Zootaxa, 2015)
Four new Species of the genus Pterodichopetala from Northeastern México are described: P. monternach n. sp., P. tuliensis n. sp., P. geovanyi n. sp., and P. robertoi n. sp. Information on distribution and ecology is provided.